Investigation of an unusual landslide at Sai Kung Sai Wan Road, Sai Kung, Hong Kong. Issue 2 (3rd April 2018) - Lo, Dominic O K; Law, Rachel H C; Wai, Roland C T; Ng, Axel K L; Williamson, Steven J; Lee, Jason K S; Cheng, Y M
ABSTRACT: An intense rainstorm on 21 May 2016 resulted a total of 34 natural terrain landslides in the vicinity of Sai Kung Sai Wan Road in the Sai Kung East Country Park, Hong Kong. One of these landslides was a large-scale failure with a source volume of about 2100 m 3 . It was almost an order of magnitude larger than all the others. The debris severely eroded a road embankment, undermining the road and resulting in road closure. The nature of the landslide was unusual in that it was a structurally controlled rockslide, with a basal failure surface formed from a persistent, planar sheeting joint within columnar jointed tuff rock with a maximum depth of about 12 m, while the other landslides that occurred in the country park during the same rainstorm involved only shallow failures within the regolith. An investigation of this unusual landslide was undertaken to diagnose the probable mechanism and causes of the failure. As there was concern about further large-scale instability occurring in the adjacent hillside where the sheeting joint was inferred to extend into, the potential for further large-scale instability was assessed as part of the investigation. The key components of the investigation included detailed engineering geological mapping, ground investigation and engineering analyses. This paper presents the findings of the investigation.